Epilepsy in Tuberous Sclerosis: Phenotypes, Mechanisms, and Treatments - Saxena, Anurag; Sampson, Julian R. (Seminars in Neurology, 2015)
Epilepsy affects 75% to 90% of people with tuberous sclerosis, a multisystem genetic disorder. Although seizures can occur for the first time at any age, onset in infancy or childhood is usual. Around 30% of patients present with infantile spasms that often respond well to treatment with vigabatrin. Later seizures may occur as specific patterns, such as in Lennox–Gastaut syndrome, or with combinations of seizures including focal and multifocal seizures, and drop attacks. Most patients have two or more seizure types. Seizure control using current antiepileptic drugs is often unsatisfactory, leading to frequent polypharmacy. Epilepsy surgery has a place in the management of some patients. Mutations in the TSC1 and TSC2 genes that cause tuberous sclerosis lead to hyperactivation of signaling via the mammalian target of rapamycin complex 1 (mTORC1). Inhibitors of mTORC1 have recently been shown to be effective treatments for some manifestations of tuberous sclerosis; they are now being assessed as potential novel antiepileptic drugs in tuberous sclerosis and related disorders.
Keywords: tuberous sclerosis; TSC1; TSC2; mTORC1; epilepsy